Analisis Pembudayaan Gemar Membaca Sebagai Kajian Pembentukan Perda Di Kabupaten Sumbawa - Safitri, Ade; Haryanto, Iwan; Rahim, Abdul; Musahrain, Musahrain; Nurhairunnisah, Nurhairunnisah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2021)
This study aims to find out and examine the foundations for cultivating a love of reading as material for the preparation of regional regulations. This study uses a legal research methodology with the approaches used in this research, namely the statutory approach, the case approach, and the conceptual approach. The data collection techniques used in this research are observation, document study and interviews. The results of the study indicate that the basis for the formation of regional regulations is based on philosophical, sociological and juridical studies.